Factors influencing adherence to antituberculosis treatment: A cross-sectional study at Sendang Agung Health Center, Central Lampung - Nabila, Sofia Zahra; Windari, Nurul Irna; Sarmoko (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2022)
This study investigates factors influencing adherence to antituberculosis treatment among pulmonary tuberculosis patients at Sendang Agung Health Center. Using a cross-sectional approach and purposive sampling, data were collected from 53 patients treated between January and March 2023. The study employed validated questionnaires and statistical analyses, including Chi-Square and logistic regression tests. The results showed that 33 patients (62.3%) were compliant with using antituberculosis drugs, while 20 patients (37.7%) were not compliant. Results indicate that factors such as age, gender, education, and employment status do not significantly affect treatment adherence. However, knowledge and treatment duration were found to be significant determinants, with knowledge being the most dominant factor (p = 0.004, OR = 16.029). The findings suggest that enhancing patient education and support systems is crucial to improving adherence and treatment outcomes. Further efforts are needed to increase awareness and ensure effective utilization of available healthcare services.